Sobre los orígenes y las confusiones terminológicoconceptuales de los términos de "aspecto"y de "Aktionsart" - Pawlak, Aneta (Wydawnictwo Naukowe UAM, 2008)
The paper presents, on the one hand, various terms that assign the categories of aspect and Aktionsart and, on the other hand, emphasizes that the concepts regarding them are not homogeneous. The confusions are supposed to have originated in the past. Therefore, we'll sketch briefly the history of aspect and Aktionsart in order to show that the term and the concept of aspect should be related exclusively to the Slavonic languages.
The origins and confusions regarding terms and concepts of aspect and Aktionsart
Keywords: aspect; Aktionsart; Slavonic languages